Is a picture really worth a thousand words? : some philosophical reflections on perceptual content - Saliba, Ruth R (Department of Philosophy, 2023)
The challenge presented by this paper is twofold; the first is to show that theories of perception ride a seesaw which is unsatisfactory, the second is to present a way to dismount the seesaw that these theories ride. The proposed dismount is suggested in the form of nonconceptual content of perceptual experiential states. In part A of the paper the seesaw metaphor is set up by showing that theories of perception concern themselves mainly with two questions. One of these questions is the epistemic question, which inquiries into the justificatory role played by perceptual experiential states. Such inquires conclude that the content of perceptual experiential states is conceptual. The other question is the descriptive question, which inquiries into the nature of perceptual experiential states. Such inquires conclude that the perceptual experiential states are not conceptual. The seesaw effect comes to play because theories of perception deal with the epistemic and the descriptive questions in isolation of each other. Part B of the paper shows how the theories of perception ride the seesaw. On the one side of the seesaw there are theories of perception that claim that perceptual experiential states are contentless. Bertrand Russell's account of sense-data is used to illustrate such theories. It is shown that while these theories are phenomenologically plausible, they are incapable of accounting for the justificatory role perceptual experiential states need to play. On the other side of the seesaw there are theories of perception that claim that perceptual experiential states have content. The account of conceptualism by John McDowell is used to illustrate the position of such theories. These theories are inadequate in accounting for the phenomenological aspect of perceptual experiential states while they are able to account for the epistemological role played by perceptual states. This is what I call riding the seesaw. Riding the seesaw does not allow any room for progress for a theory of perception. Part C of this paper suggests a way of dismounting the seesaw by considering the notion of nonconceptual content of perceptual experiential states. The paper acknowledges that work is still necessary to sharpen the notion of nonconceptual content of perceptual states. However, nonconceptual content of perceptual experiential states is put forward as a better alternative in the light of the discussions in parts A and B.